VALIDITY ANALYSIS OF STEM-BASED E-LWS WITH PBL MODEL ON MOTION KINEMATICS MATERIAL TO SUPPORT CRITICAL THINKING SKILLS OF SENIOR HIGH SCHOOL STUDENTS - Wedy, Zahra Salsabila; Ratnawulan, Ratnawulan; Desnita, Desnita; Yumna, Hayyu (PILLAR OF PHYSICS EDUCATION, 2025)
This research is motivated by the rapid development of technology from various fields, one of which is in the field of education. In the world of education, this technology has an important role in the continuity of the learning process. The use of electronic-based teaching materials is one of the utilization of technology in the learning process. One of the teaching materials that can be used is the Electronic Learner Worksheet (E-LWS). The purpose of the research is to make STEM-based electronic student worksheets with PBL models on motion kinematics material to support the critical thinking skills of SMA/MA students. The creation of Learner Worksheets is expected to be not only valid in terms of content and structure but also effective in facilitating a more meaningful learning experience for students. This research used the Research and Development (R&D) method. The validation process was carried out by three physics lecturers from Padang State University (UNP). Analysis of the results of the validation instrument showed that the developed Learner Worksheet obtained a validation score of 0.95. The score obtained is included in the "valid" category. Therefore, the product made in this study STEM-based Learner Worksheets with PBL model is considered valid and suitable for use as one of the innovative teaching materials to support students' critical thinking skills in understanding motion kinematics material.